2017
DOI: 10.1007/s00253-017-8604-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between metabolically active and dormant bacteria on paper

Abstract: Switching between metabolically active and dormant states provides bacteria with protection from environmental stresses and allows rapid growth under favorable conditions. This rapid growth can be detrimental to the environment, e.g., pathogens in recreational lakes, or to industrial processes, e.g., fermentation, making it useful to quickly determine when the ratio of dormant to metabolically active bacteria changes. While a rapid increase in metabolically active bacteria can cause complications, a high numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The metabolic activity of bacteria has been monitored to evaluate bacterial respiration (e.g. using tetrazolium salts that change color when organic matter (OM) is oxidized (Hice et al, 2018; Roslev and King, 1993)). This rapid colorimetric technique may also serve as an approach to demonstrate that biodegradable organic substrate is available to viable bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic activity of bacteria has been monitored to evaluate bacterial respiration (e.g. using tetrazolium salts that change color when organic matter (OM) is oxidized (Hice et al, 2018; Roslev and King, 1993)). This rapid colorimetric technique may also serve as an approach to demonstrate that biodegradable organic substrate is available to viable bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction by the Whitesides group in 2007, microfluidic paper-based analytical devices (PADs) have become an expanding research field with applications encompassing a breadth of scientific disciplines [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. A wide array of fabrication processes has been detailed in the literature as have detection techniques focused mainly on colorimetric types.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ox‐PPE is capable to differentiate live bacteria from dead bacteria and can be potentially used to detect slow‐growing bacteria. [ 19 ]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ox-PPE is capable to differentiate live bacteria from dead bacteria and can be potentially used to detect slow-growing bacteria. [19] We then moved forward to study what metabolic products cause the reduction of ox-PPE. Previously, we have demonstrated that the broad-absorbing conjugated polymer could be imaged with a transient-absorption (TA) microscope.…”
Section: (4 Of 10)mentioning
confidence: 99%